2020
DOI: 10.1016/j.psj.2019.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic alteration of albumen by dietary vanadium in commercial egg-type layers

Abstract: Vanadium ( V ) is an ultratrace metal with the insulin-tropic properties and is often researched as the diabetes drug. However, in animals, V has been reported to have toxic effects on the development, immunity, oxidation–reduction equilibrium, gastrointestinal function, and so forth. Especially in poultry, supplementation of more than 10 mg of V/kg in the layer diets has been shown to adversely affect the egg production and egg quality. In this study, we supplemented 0 mg of V/kg, 5 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Further, diet-induced oxidative stress may degrade albumen proteins and invariably albumen quality. One study reported that vanadium-based diet caused a reduction in albumen quality by decreasing the abundance of an egg white protein; lysozyme (Q6LEL2) which possesses antimicrobial properties while increasing protease inhibitors that restrain activities of some proteins (87). It is crucial to enhance endogenous antioxidant enzymes in order to mitigate the adverse effects of oxidative stress on animal and its product as well.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Further, diet-induced oxidative stress may degrade albumen proteins and invariably albumen quality. One study reported that vanadium-based diet caused a reduction in albumen quality by decreasing the abundance of an egg white protein; lysozyme (Q6LEL2) which possesses antimicrobial properties while increasing protease inhibitors that restrain activities of some proteins (87). It is crucial to enhance endogenous antioxidant enzymes in order to mitigate the adverse effects of oxidative stress on animal and its product as well.…”
Section: Oxidative Stressmentioning
confidence: 99%